2008
DOI: 10.1021/cm8023633
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Layer-by-Layer Hydrogels with Incorporated Gold Nanorods as pH-Sensitive Optical Materials

Abstract: We report ultrathin pH-responsive plasmonic membranes of [poly(methacrylic acid)-gold nanorods] 20 (PMAA-Au NRs) 20 with gold nanorods embedded into swollen cross-linked LbL hydrogels. In contrast to the most of known pH responsive materials which rely on pH-triggered change in the intensity of photoluminescence or plasmon bands, the responsive structures suggested here exhibit a significant pHtriggered shift in easily detectable, strong plasmon resonance band. We show that a pH-induced deswelling of the (PMAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
144
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 79 publications
3
144
0
Order By: Relevance
“…P3HT possesses excellent solution processability, environmental stability, high charge-carrier mobility, and tailorable electrochemical properties. [2] Owing to their quantum-confined nature, for quantum dots (QDs) such as cadmium selenide (CdSe), [3] variation of the nanocrystal size provides continuous and predictable changes in fluorescence emission, [4,5] thus rendering them useful for a wide range of applications in photovoltaic cells, [6,7] LEDs, [8] biosensors, [9] and bio-imaging. [9] CP-based organic/inorganic hybrid solar cells (e.g., CP/QD composites) are favorable alternatives to inorganic solar cells as they have many advantages peculiar to CPs, such as light weight, flexibility, processability, roll-to-roll production, low cost, and large area.…”
mentioning
confidence: 99%
“…P3HT possesses excellent solution processability, environmental stability, high charge-carrier mobility, and tailorable electrochemical properties. [2] Owing to their quantum-confined nature, for quantum dots (QDs) such as cadmium selenide (CdSe), [3] variation of the nanocrystal size provides continuous and predictable changes in fluorescence emission, [4,5] thus rendering them useful for a wide range of applications in photovoltaic cells, [6,7] LEDs, [8] biosensors, [9] and bio-imaging. [9] CP-based organic/inorganic hybrid solar cells (e.g., CP/QD composites) are favorable alternatives to inorganic solar cells as they have many advantages peculiar to CPs, such as light weight, flexibility, processability, roll-to-roll production, low cost, and large area.…”
mentioning
confidence: 99%
“…They also showed that the swelling behavior of the brush was not affected by the presence of the nanoparticles. Similarly Kozlovskaya et al used nanorods incorporated into thin (55 nm) layer-by-layer hydrogels to detect pH changes [49] .…”
Section: Polymer Swellingmentioning
confidence: 99%
“…Specifically, poly(N-isopropylacrylamide) (PNIPAAm) and poly(methylacrylic acid) (PMAA) have been focused on thermo-and pH-sensitive behavior [4][5][6]. Since pHsensitive carriers can target drugs to deep organs or tumor tissues, PMAA-based amphiphilic block copolymer micelles have widely been investigated for these applications.…”
Section: Introductionmentioning
confidence: 99%